The MCH Handbook Piloting in Sierra Leone: A Case Report - Fullah, Mary Augusta (Archives of Case Reports, 2026)
The Maternal and Child Health Handbook (MCHHB) is an integrated home-based record designed to strengthen continuity of care across the maternal, neonatal, and child health continuum. In Sierra Leone, where maternal, neonatal, infant, and under-five mortality rates remain among the highest globally (443/100,000; 31/1000; 72/1000; and 122/1000 live births, respectively – DHS 2019), the Ministry of Health and Sanitation (MoHS) with support from partners piloted the MCHHB from 2021 to 2022 in Moyamba, Pujehun, and Western Rural districts. This baseline survey aimed to assess clients’ characteristics, health-seeking behaviours, and understanding of maternal and child health information before full implementation. A mixed-methods design was employed, combining structured questionnaires and interviews across five intervention facilities and two control facilities, targeting 500 clients (470 respondents in intervention, 76 in control). Results revealed that 41% of clients had no education, 64% experienced their first pregnancy before 18 years, and 29% reported multiple abortions or stillbirths. Antenatal care knowledge and practice were significantly higher among target clients using the MCHHB compared to controls (81% vs. 68% knew next ANC date and purpose). Only 1% of target clients lacked understanding of MCH information versus 54% – 61% of control clients. Male involvement and discussion on pregnancy were also stronger among target clients (husbands/partners: 81% vs. 38%). The findings suggest that the MCHHB enhances knowledge, improves communication between clients and health workers, and promotes a continuum of care. However, challenges including early pregnancies, high parity, socio-cultural barriers to family planning, and unstable incomes persist. The study recommends strengthening training and supervision of frontline workers, ensuring enabling environments for handbook use, engaging community health workers for follow-up, and introducing portable technologies such as ultrasound for improved maternal care.